Livedo retikularis pada penderita Granulomatosis Wegener SUATU LAPORAN KASUS. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Elly Moedijatmini, Bambang Setyo, Fadjar Waskito â Livedo reticularis in a patients with Wegener Granulomatosis. A case report. Livedo reticularis (LR) is a skin lesion which is characterized by a reddish blue mottling in a fishnet reticular pattern. Although many diseases have been considered as causative of LR, Wegener's Granulomatosis (WG) has never been reported to be associated with LR. A case of LR was reported in a 70-year-old woman suffering from WG. However, it is difficult to conclude whether LR is a part of WG or only a coincident case. The vasculitis features as shown by histopathological skin examination suggest that the skin lesion might be a part of WG syndrome.